Analyzed The Students Need to Reduce Ineffective Readers Through Scientific Books - Caltira Rosiana; Sujono (STKIP PGRI Nganjuk, 2018)
The target of goal in this study analyzed the instructional documents’ problem in teaching branch linguistic aspect such as morpheme, syntax, linguistic, semantic, sociolinguistic etc. The second target analyzed the lecturers’ complication to stimulate the students’ motivation in linguistic area. The last target is analyzed the students’ need to achieve their knowledge in all of linguistic area. The researchers conducted this research as Collaborative Classroom Action Research (CCAR) because the researchers do it in a team. This research is the revolution of English study toward Productive Reading Technique which combines all of the English skill such as reading, speaking, writing and listening. The researcher designed this technique based on the students’ need and the newest standard curriculum. The researchers selected the sample as purpossive technique sampling for the students who are taking the sociolinguistic subject. Getting the real information toward observations, spread out questionnaire paper and interview all of subject learning is the important instrument in this research. In this study, the researcher used some stages in collecting data, namely: collecting data from all aspect, tabulation, data analyzed, and making result based on the data collections. From the information above, the researchers got result that all of the branch of linguistic area still used old method such as speech form lecturer and boring discussion, the lecturer need renew their sources leaning based on the latest curriculum and students’ need, more than 70 % the students explain that they need the new book which relevance with the newest knowledge and method.